Estimation of the number of neurons in the hippocampus of rats with penicillin induced epilepsy - Akdogan, Ilgaz (Image analysis and stereology, 2002)
Epilepsy is a neurological disease arising from strong and uncontrollable electrical firings of a group of neurons in the central nervous system. Experimental epileptic models have been developed to assess the physiopathology of epileptic seizures. This study was undertaken to estimate the number of neurons in the rat hippocampus with penicillin induced epilepsy,using a stereological method, "the optical fractionator". In the experimental group, 500 IU penicillin-G was injected intra-cortically, and in the control group, the same volume of saline was administered. A week later, the animals were decapitated and their brains were removed by craniatomy. Frozen brains were cut with a thickness of 150 pm in a cryostat. Sections werecollected by systematic random sampling and stained with hematoxylen-eosin. Microscopic images of pyramidal cell layers from hippocampus CA1, CA2 and CA3 subfields were then transferred to a monitor, using a 100x objective (N.A. = 1.25). Using the optical disector method, the neurons were counted in the frames and determined with a fractionator samplingscheme. The total pyramidal neuron number was then estimated using theoptical fractionator method. The total pyramidal neuron number was found tobe statistically lower in the experimental group (mean = 142,888 +- 11,745) than in the control group (mean = 177,953 +- 10,907) (p < 0.05). 'The results suggest that a decrease in the hippocampal neuronal number in a penicillin model of epilepsy can be determined objectively and efficiently using the optical fractionator method.
Keywords: Epilepsija; Epilepsy; Hipokampus; Chemically induced; Nevroni; Penicillins; Penicilini; Neurons; Celica, štetje; Hippocampus; Anatomy and histology; Podgane, Sprague-Dawley; Rats, sprague-dawley; penicillin; penicilin; podgane; Cell count